CUMULATIVE POISONS & ITS MANAGEMENT WITH SPECIAL REFERENCE TO DUSHI VISHA - Kishor, *Mishra Awadh; Anita, Sharma; Sharad M., Porte; Rohit, Khatik (International Journal of Ayurveda and Pharma Research, 2016)
Bio-accumulation is the buildup of substances within the body. This is a necessary process for nutrients within the body like vitamins, minerals, and amino acids. On occasion, some harmful substances enter the body and bio-accumulate. These are cumulative Poisons, not immediately eliminated from the body. They tend to bio-accumulate in the system and can produce symptoms of chronic poisoning. Most of these substances are found in the Environment, or come from the food that we eat or water we drink. Now A day the sources of poisons are not limited, as in the days of classics. Generally, human beings are exposed to different poisons via ingestion (drinking or eating) & inhalation (breathing). In recent years, the burden of chronic toxin accumulation as a cumulative poison in form of Dushi visha has become clearer & more disturbing. Dushi Visha like cumulative poison is slow acting poison, which have not been fully eliminated from the system. It is retained in the tissues of living beings for a number of years; it contaminates the tissues, and is therefore called Dushi visha. Bio-accumulation of these cumulative poisons causes diseases in living beings. A patient afflicted with the cumulative poisons should be first take careful history & then proper clinical examination we manage it using principles of Ayurveda i.e. Nidana Parivarjan / Preventive measure , Bio-purification & using supplementary medication in form of Agad as mention in our classical text.